Cymbella biseriata sp. nov.—a unique living species of Cymbella Agardh (Bacillariophyceae) with biseriate striae - VIDESKA, ANASTASIJA; ZAOVA, DUŠICA; NAUMOVSKA, HRISTINA; KOCHOSKA, HRISTINA; Mitic Kopanja, Danijela; Levkov, Zlatko (Magnolia Press, 2022)
Alpine ponds are known biodiversity hot-spots and refugia for many rare and endangered species. They are also considered to be vulnerable habitats in terms of acidification, eutrophication, modification and climatic changes. Recently, a detailed study of diatoms in these habitats in North Macedonia has been started to evaluate their status and threats. During these studies, specimens of a species of Cymbella that lacked apical pore fields and had a small valve size were recorded. Scanning electron microscope observations revealed biseriate striae composed of small, slit-like to tilde-like areolae, a character so far not observed in any living representatives of the genus Cymbella. Herein, these specimens are assigned to the new species Cymbella biseriata sp. nov. based on detailed observations with light and scanning electron microscope. Comparison with similar taxa from the C. helvetica species complex and fossil species with biseriate striae is provided.